Literasi Digital Merangkul Teknologi Membekali Siswa di Era Digital pada SMA N 12 Tanjung Jabung Barat - Fitra Kebesa Miten; Arif Setiadi; Sugeng Wibowo; Fadhli Azis; Telly Zuvilla Irwanto; Arie Agus Setiawan (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2025)
The development of information and communication technology in Indonesia continues to grow rapidly, as evidenced by the internet penetration rate reaching 73.3% in 2019 (APJII). With 144.19 million out of 196.71 million Indonesians having internet access, the country has become the largest digital economy market in Southeast Asia (Google e-Conomy SEA, 2020). West Java Province recorded the highest number of internet users, followed by Central Java, DKI Jakarta, and Jambi. In response to this development, President Joko Widodo has designated accelerating digital transformation towards becoming a "digital nation" as one of the main visions of his administration, focusing on the development of digital talent human resources. This program emphasizes the importance of digital literacy, which includes individuals' ability to access, understand, create, communicate, and evaluate digital technology (UNESCO, 2018). The Minister of Communication and Information Technology targets digital literacy for 12.5 million Indonesians by 2020–2024 to enhance cognitive abilities beyond merely operating devices. In this context, lecturers from the Institute of Technology and Business Pelita Raya launched a community service activity on digital literacy themed "Embracing Technology: Equipping Students in the Digital Era at SMA N 12 Tanjung Jabung Barat." This activity aims to equip students with relevant digital skills to face the challenges of the digital era and contribute to Indonesia's digital transformation.